African Union, Promotion of Democracy and Anti-Corruption Initiatives in Africa - Ayodeji, Gafar Idowu; Kolade, Adegboyega Francis; Abiodun, Emmanuel Temitope (ABUAD Journal of Social and Management Sciences, 2023)
The African Union (AU) has been pursuing one of its primary objectives of promoting democratic principles and institutions by ensuring good governance through the curbing of corruption. It is uncertain whether the democratic approach has rubbed off on its anti-corruption initiatives, given the recent performance of most AU member states on many global surveys of corruption, development and governance evaluation indexes. The paper, therefore, examined the extent to which the AU’s stance on democratic promotion has impacted on its anti-corruption initiatives in Africa. The study is qualitative and relied on data sourced from secondary sources, while content analysis was adopted for data analysis. The findings acknowledge AU's committed advancement of democracy in Africa through its different anti-corruption frameworks. But in spite of the slight improvements of some African counties on different corruption perception indexes, corruption persists in the governance of many AU member states. The study further shows inter alia that the AU’s anti-corruption initiatives have not effectively reflected the adopted measures due to uncommon democratic ideals, legitimisation of autocratic regimes, and the fact that many African states fail to uphold their obligations under the AU's anti-corruption convention. The study contends that AU’s anti-corruption bodies should ensure and encourage member states to internalise and uphold existing governance norms and accountability measures, while implementation mechanisms should be strengthened.